Biophilia: residents’ connection with green infrastructure in a town - Mansor, Mazlina (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
Green infrastructure is urban nature consisting of greenery and green spaces distributed in and around town. It facilitates residents’ contact with natural environment that may fulfil their needs for nature in urban places. Human’s inherent affiliation with the natural environment or Biophilia has been long hypotesised. The paper draws the findings of a case study exploration on the connection between residents with green infrastructure in Taiping, a small colonial town in Peninsular Malaysia. Biophilic tendency of residents to green infrastructure in the town was elicited using questionnaire survey (n=335) and semi-structured interviews (n=33). The results show that residents who participated in activities within the greenery and open spaces in the town experienced various benefits that fulfil their needs for nature. Physically, participating in activities provided the residents active living. Physical and visual experience afforded relaxation, comfort and calmness. More social interactions were experienced resulting in community satisfaction. The study concludes that existence of matured green infrastructure extends beyond aesthetic enjoyment. It provides urban residents with a connection to nature that induces affiliation with green infrastructure in a town. Thus, planning and provision of green infrastructure with care by urban planners and designers are essential in the urban fabrics.